2018
DOI: 10.1089/end.2018.0395
|View full text |Cite
|
Sign up to set email alerts
|

Caliceal Fluid Temperature During High-Power Holmium Laser Lithotripsy in an In Vivo Porcine Model

Abstract: High-power holmium laser settings (40 W) can induce potentially injurious temperatures in the porcine in vivo model, particularly with slower irrigation rates. Characterization of thermal dose across a broader range of laser parameter settings is underway to map out the thermal safety envelope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(58 citation statements)
references
References 14 publications
3
55
0
Order By: Relevance
“…Reducing the frequency and, therefore, the total power during lithotripsy is of importance to limit the risk of thermal injury from heat generation. 26,27 In conclusion, the results of this in vitro study demonstrated that there is a frequency threshold after which increasing the pulse frequency leads to minimal gain in ablation when the laser fiber is fixed. When the fiber is moving, increasing the frequency increases fragmentation, but also only until a specific higher frequency threshold is reached.…”
Section: Figmentioning
confidence: 61%
“…Reducing the frequency and, therefore, the total power during lithotripsy is of importance to limit the risk of thermal injury from heat generation. 26,27 In conclusion, the results of this in vitro study demonstrated that there is a frequency threshold after which increasing the pulse frequency leads to minimal gain in ablation when the laser fiber is fixed. When the fiber is moving, increasing the frequency increases fragmentation, but also only until a specific higher frequency threshold is reached.…”
Section: Figmentioning
confidence: 61%
“…Innovations in laser development resulted in the introduction of high power Ho:YAG lasers on the market, providing an average power around 100W, which can be very efficient in stone destruction [35][36][37]. Furthermore, attention should in particular also be dedicated to heat generation inside the urinary tract when using such high power laser devices [38][39][40][41][42]. Fluorescence-assisted endoscopic laser lithotripsy should be introduced in particular in connection with high power laser devices.…”
Section: Propulsiomentioning
confidence: 99%
“…As this wavelength is so strongly absorbed by water, it can damage the surrounding tissue. While severe direct physical lesions occur seldom, there is increasing evidence that secondary thermal injuries due to excessive temperatures in the upper urinary tract can become dangerous [6][7][8]. The Ho:YAG laser's therapeutic range in aqueous liquid is about 1-5 mm, and the release of high energetic pulses depends solely on the surgeon.…”
Section: Introductionmentioning
confidence: 99%